The Role of Internal Control in Risk Management: A Systematic Literature Review - Fitria Heny Widyastuti; Yuyun Syafithri; Danti Sagita; Rela Sari (PT FORMOSA CENDEKIA GLOBAL, 2025)
In an increasingly complex and unstable business environment, internal control has become a crucial element in ensuring the effectiveness of risk management and strong corporate governance. This study conducts a Systematic Literature Review (SLR) of 20 peer-reviewed scientific articles published between 2000 and 2025 and indexed by Scopus, aiming to examine the role of internal control in organizational risk management across both financial and non-financial sectors. The findings indicate that the presence of high-quality internal control systems significantly enhances an organization's ability to identify, assess, and mitigate various types of risks including financial risks, legal litigation, stock price crashes, and weaknesses in financial reporting. The literature demonstrates that when internal control systems are well-designed and effectively implemented, they act as a strategic tool rather than merely an administrative mechanism.